2008
DOI: 10.2337/dc07-1207
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Diabetes and Cardiovascular Risk Factors Associated With Urbanization in India

Abstract: OBJECTIVE -To compare prevalence of diabetes, impaired glucose tolerance (IGT), impaired fasting glucose (IFG), and cardiovascular risk factors between a city, a town, and periurban villages (PUVs) in southern India and to look for temporal changes in the city and PUVs.RESEARCH DESIGN AND METHODS -Subjects aged Ն20 years were studied in Tamilnadu, India, in Chennai (city, n ϭ 2,192; 1,053 men and 1,138 women), Kanchipuram (town, n ϭ 2,290; 988 men and 1,302 women), and Panruti (PUVs, n ϭ 2,584; 1,280 men and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
232
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(262 citation statements)
references
References 22 publications
23
232
6
1
Order By: Relevance
“…Abdominal obesity was the most common abnormality in the different groups. Several epidemiological studies in native Asian-Indians [4,8] and migrant Indians [9] have shown a higher occurrence of upper body adiposity than general adiposity (BMI).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abdominal obesity was the most common abnormality in the different groups. Several epidemiological studies in native Asian-Indians [4,8] and migrant Indians [9] have shown a higher occurrence of upper body adiposity than general adiposity (BMI).…”
Section: Discussionmentioning
confidence: 99%
“…Normoglycaemic individuals were selected from the database of a diabetes survey conducted by us in 2006 in a city, a town and villages [4]. In brief, an epidemiological survey of diabetes and prediabetic states (impaired glucose tolerance and impaired fasting glucose) was performed in the city of Chennai, Kanchipuram town, and villages of Panruti (19 villages randomly selected out of 42) in Tamil Nadu, India.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of this marker, however, is known to vary among populations, influenced by gender, age, and obesity [7]. South east Asians are known to be at a high risk for T2DM, CVD, and MetS [8,9]. There has been a paucity of evidence from this part of world including Nepal regarding hsCRP level in health and diseases.…”
Section: Introductionmentioning
confidence: 99%